Performance Audit of National Rural Health Mission (NRHM) in Kerala - CAG of India (CAG of India, 2009)
The National Rural Health Mission was launched by Government of India in April 2005 for strengthening rural health care institutions by providing adequate infrastructure facilities and funds. In Kerala, the State Health Mission was set up in September 2006. A review of the implementation of the National Rural Health Mission in Kerala for the period 2005-06 to 2008-09 revealed improvements in the flow of funds to rural health institutions, upgradation of infrastructure in some health institutions and better health awareness among the rural population. Although sample household surveys were carried out in the three test-checked districts, facility surveys required to identify health care needs of rural areas were conducted only in Community Health Centres though the guidelines stipulated that these were also to be carried out in Primary Health Centres and Sub Centres. The Perspective Plan for the Mission period was not prepared. During 2007-08 and 2008-09, National Rural Health Mission funds of Rs 1.48 crore were spent on activities not approved by Government of India in the annual Programme Implementation Plans and Rs 51.86 lakh was diverted without their approval. Accredited Social Health Activists selected during 2007-08 and 2008-09 were not imparted training in three out of five prescribed modules. Availability of manpower, infrastructure and equipment in Community Health Centres and Primary Health Centres did not meet the Indian Public Health Standards. Guidelines for procurement of medicines prescribed by Government of India were not followed. Penalty of Rs 3.18 crore for delayed supplies of medicines was not levied. An effective Health Management Information System was not set up even though hardware and software valuing Rs 4.70 crore were procured for this purpose. Under the 'Integrated Disease Surveillance Project', hardware and accessories procured for Rs 54.82 lakh for video-conferencing units at the district level were lying idle as the State level video-conferencing unit had not been set up due to non provision of space by the Director of Health Services.
For the Period 2005-06 to 2008-09